SPATIAL CONTROL POLICY TO REALIZE THE CONCEPT OF SUSTAINABLE DEVELOPMENT - Budi Arif Musliman; Edi Pranoto (Jurnal Darma Agung, 2022)
Increasing land use activities has an impact on changes in land use which can disrupt sustainability which has an impact on disrupting the concept of sustainable development. This article discusses the concept of spatial control policies to realize the concept of sustainable development. By using the method of normative juridical approach, with the specification of analytical descriptive research which is sourced from secondary data, primary legal materials, a spatial control policy is produced which is very important and urgent to strictly implement the mandate of the Law on Spatial Planning. Spatial planning policy synchronization must be carried out so that there are no overlapping policies between the government, provincial government and district government. Compliance with the Spatial Planning Law and its derivatives will be able to realize the concept of sustainable development, in which in the end development is not only for present interests but also for future interests. Welfare which is the goal of the government will be realized as mandated by Paragraph 4 of the 1945 Constitution of the Republic of Indonesia.